Nature Resources Contestation Between Native Papuans: Establishing a Collaborative Management of the Cyclops Mountain Nature Reserve Area in Papua, Indonesia - Marthen, Fadli; Gunawan, Budhi; Soemarwoto, Rini; Palar, Miranda Risang Ayu (Jurnal Manajemen Hutan Tropika, 2024)
Natural resource management and biodiversity protection in conservation areas require the involvement of local communities. However, these efforts are often hampered by conflicts in the use of resources among the population, including among the indigenous people. In this regard, this study examines the contestation of the management and utilization of natural resources between local indigenous Papuans and indigenous Papuan migrants in the Cyclops Mount Nature Reserve (CMNR). The study explored a wide range of information related to this issue qualitatively by using a mini-ethnography method. The study conducted in-depth interviews with informants from local and migrant communities and participant and non-participant observations. The study shows that the local indigenous Papuan utilized the area on a relatively sustainable basis. However, they were not able to prevent the use of natural resources in the CMNR by the indigenous Papuan migrants, resulting in environmental damage. To avoid further environmental damage to the CMNR, this study recommends the need for collaborative management of the CMNR area by involving both local indigenous Papuans and indigenous Papuan migrants with support from the government.